Developmental bias in the evolution and plasticity of beetle horn shape. Issue 1983 (28th September 2022) - Rohner, Patrick T.; Hu, Yonggang; Moczek, Armin P.
Abstract : The degree to which developmental systems bias the phenotypic effects of environmental and genetic variation, and how these biases affect evolution, is subject to much debate. Here, we assess whether developmental variability in beetle horn shape aligns with the phenotypic effects of plasticity and evolutionary divergence, yielding three salient results. First, we find that most pathways previously shown to regulate horn length also affect shape. Second, we find that the phenotypic effects of manipulating divergent developmental pathways are correlated with each other as well as multivariate fluctuating asymmetry—a measure of developmental variability. Third, these effects further aligned with thermal plasticity, population differences and macroevolutionary divergence between sister taxa and more distantly related species. Collectively, our results support the hypothesis that changes in horn shape—whether brought about by environmentally plastic responses, functional manipulations or evolutionary divergences—converge along 'developmental lines of least resistance', i.e. are biased by the developmental system underpinning horn shape.